Os Relatórios do Desenvolvimento Humano (RDHs) e o padrão de intervenção pública na área social: os desafios postos à forma de organização do Estado no Brasil - Maria José de Rezende (Estudios Sociales)
The HDRs systematize a set of proposals that undergo the redefinition of the state intervention pattern in the social area. They propose changes in policies for education, health and sanitation. These are general proposals that attempt to find common and viable solutions for several countries in Africa, Latin America and Asia. The reports show, over hundreds of pages, examples of social policies that have been implemented in various parts of the world. This study aims to demonstrate both the social policy suggestions contained in the HDRs, and the difficulties faced by such proposals in Brazil, where the main binding in the redefinition of forms of intervention in the social area, consists of a political logic that does not dismantle a model of income transfer which strengthens the concentration of resources and power. Changing the orientation of the State actions is the biggest political challenge posed to the segments (civil society organizations, political leaders, social movements, associations, intellectuals) that fight for a more inclusive and equitable pattern of social organization.